2018
DOI: 10.2139/ssrn.3155776
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analyses Identify KIF5A as a Novel ALS Gene

Abstract: To identify novel genes associated with ALS, we undertook two lines of investigation. We carried out a genome-wide association study comparing 20,806 ALS cases and 59,804 controls. Independently, we performed a rare variant burden analysis comparing 1,138 index familial ALS cases and 19,494 controls. Through both approaches, we identified kinesin family member 5A (KIF5A) as a novel gene associated with ALS. Interestingly, mutations predominantly in the N-terminal motor domain of KIF5A are causative for two neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
239
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(247 citation statements)
references
References 84 publications
8
239
0
Order By: Relevance
“…By doing the clinical correlation analysis, a clinically significant intronic variant in KIF5A , a heterozygous, c.3020+3 A>T change which was predicted to be a potentially splice site change was identified to be segregating with the affected individuals only. This was a novel DNA variant in KIF5A ; a variant, c.3020+3 A>G (NM_004984) at the same site has been reported by Nicolas et al and was not reported in 1000 Genome, ExAC and gNOMAD dataset and also it was absent in our in‐house cohort of 300 exomes of Indian individuals referred for various genetic diseases. This variant is located near 3′ donor splice site of the exon 27 of KIF5A .…”
supporting
confidence: 72%
See 1 more Smart Citation
“…By doing the clinical correlation analysis, a clinically significant intronic variant in KIF5A , a heterozygous, c.3020+3 A>T change which was predicted to be a potentially splice site change was identified to be segregating with the affected individuals only. This was a novel DNA variant in KIF5A ; a variant, c.3020+3 A>G (NM_004984) at the same site has been reported by Nicolas et al and was not reported in 1000 Genome, ExAC and gNOMAD dataset and also it was absent in our in‐house cohort of 300 exomes of Indian individuals referred for various genetic diseases. This variant is located near 3′ donor splice site of the exon 27 of KIF5A .…”
supporting
confidence: 72%
“…Genetic defects in KIF5A gene has been implicated in wide range of neurodegenerative phenotype, length‐dependent axonopathies, that is, hereditary spastic paraplegia (SPG10) and Charcot‐Marie‐Tooth disease (CMT2), and motor neuron disease . It has been hypothesized that location of KIF5A variants are determinant of this differential phenotypic manifestations.…”
mentioning
confidence: 99%
“…Therefore, the p.F1023C mutation might be associated with both ALS and HSP; further studies are needed to ascertain the mechanism. Two splice site mutations found in the current study were also described in Caucasian ALS population,3 which suggests that these splice site mutations may be a common cause for ALS both in the Caucasian and Chinese populations. Among these patients carrying the C-terminal cargo binding domain in KIF5A reported in our study and previous studies,3 4 most of them showed a late age of onset, except three patients who had an age of onset younger than 40 years old.…”
Section: Discussionsupporting
confidence: 71%
“…The publicly available GWAS summary statistics for ALS included up to 20,806 cases and 59,804 controls of European ancestry . All 20,806 probable or definite ALS patients diagnosed by a neurologist specializing in ALS according to the EI Escorial criteria were included in the case cohort study …”
Section: Methodsmentioning
confidence: 99%